Tinjauan Literatur: Penerapan Teknologi Blockchain dalam Sistem Verifikasi Sertifikat Akademik - Wisnu Rizki Ferdiansyah; Safani Nur Awal; Muhamad Tsaqif (Program Studi Teknik Informatika Universitas Paramadina, 2026)
This study evaluates the application of blockchain technology to address academic certificate forgery using a Systematic Literature Review (SLR) based on PRISMA guidelines (2022–2025). Analysis of seven selected studies reveals that the most effective architecture is a hybrid model combining public blockchain (Ethereum) and off-chain storage (IPFS) integrated with QR Codes. This implementation is proven to guarantee data immutability and reduce verification time to seconds. However, due to high transaction costs and privacy issues, future research is recommended to focus on consortium blockchain or Layer-2 solutions.